Research progress and trends of insect high-temperature stress: insights from bibliometric analysis - Li, Jiapeng; Wang, Xianting; Guo, Rui; Li, Zikun; Lv, He; Wang, Yiping (Frontiers in Insect Science, 2025)
Climate warming, particularly extreme temperature events, poses a major threat to insect survival and diversity. Thus, understanding insect responses to high temperatures is increasingly important for predicting their resilience and distribution under climate change. In this study, we analyzed 4,417 articles from the Web of Science Core Collection using VOSviewer, CiteSpace, and the Bibliometrix R package. The results show that since 2012, the number of publications on insect responses to high temperatures has been increasing year by year at an average annual growth rate of 3.5%, reflecting the increasing research interest in this field. Secondly, the response of insects to high temperatures is a multidisciplinary research field. The PLoS One journal has the largest quantity of published articles, boasting the highest total citations and H-index globally. Hoffmann AA and Du YZ are the most productive authors. Furthermore, keyword analysis revealed research focus on molecular responses such as gene expression and heat-shock proteins. Cluster analysis of bibliographic coupling identified 15 major research themes, results demonstrate that the field evolved from describing physiological traits to dissecting biochemical and reproductive mechanisms underlying thermal tolerance, aiming to uncover biological responses and adaptive strategies under heat stress. To summarize, this study provides an overview of current research trends and emerging priorities in insect heat stress biology.